Determinant Export of Indonesia Manufacturing Industry in the Long Term - Muhammad Devis Susandika; Rosanto D H (Trunojoyo University of Madura, 2021)
This study analyze determinant factors exports of Indonesian manufacturing industry such as real FDI inflows, real interest rates, and foreign income, as well as the real exchange rate IDR / USD in the period from the first quarter 2005 - Second Quarter 2019. This study uses time series data in quarterly types through VECM (Vector Error Correction Model) methods to determine the effect in a long-term. This study shows that the determinant factors of exports Indonesian manufacturing industry in the long term are real FDI inflows, foreign income and domestic domestic real interest rates. While real exchange rate IDR / USD does not significantly affect to exports of Indonesian manufacturing industry.